GENERAL GEOLOGY OF KLEDANG RANGE: IMPLICATION ON TECTONIC EVOLUTION IN KINTA VALLEY - Binti Ashari, Nashira (Universiti Teknologi PETRONAS, 2015)
Kinta Valley is characterised by the distinctly changes in slope which is due to the intrusion of Main Range Granite to the east and Kledang Range Granite to the west. Previous authors claim the fracture patterns observed in the Paleozoic rocks in Kinta Valley is due to the granite which intruded the older rocks in Triassic. However the granite itself is also fractured. Therefore, the aim of this research is to investigate the deformation history of Kinta Valley especially on the west side by focusing on the structural features and deformation patterns of Kledang Range granite. Lithology description and primary data sets such as the strike and dip for fractures are obtained by conducting fieldwork. Structural analysis were done by plotting stereographic projection and rose diagram revealed that the fracture patterns in Kledang Range granite are mostly trending NW-SE and NE-SW. The compressional forces subjected on the area come from E-W direction resulted from the collision between India and Eurasia in middle Eocene and Oligocene. Other lithologies nearby the granite area developed folding with N-S strike. It is believed that the uplifting of the granite results in the folding. Therefore this indicate that the deformation patterns observed in Kinta Valley area are due to series of geological events happened in the past, and also resulted from the localized tectonic activities. Samples taken from the outcrop are further analysed in the laboratory using thin section, x-ray diffraction and x-ray fluorescence to identify the minerals, compounds and elements in the rocks. There are indications that the granite in Kledang Range experienced different rate of cooling giving some of them phaneritic and some other porphyritic texture. In this study, phaneritic biotite granite is found in northern part of Kledang Range which is in Sungai Siput. Moving towards the south of Kledang Range, in Hutan Lipur Papan, the granite texture is porphyritic. The texture pattern is governed by the thickness of the overlying sediments.